Analisis Pengaruh Jenis -Jenis Rumah Ekonomi dalam Meningkatkan Pemahaman Siswa SMAN 12 Medan - David Christian Silitonga; Nurul Mardiah; Romauli Situmeang; Revita Yuni; Siti Sarah Tumangger (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Economic concepts are often considered abstract and difficult to understand by high school students. The lack of connection between the subject matter and the reality of everyday life is one of the factors causing low student interest in learning in this field. This study aims to explore the effectiveness of the